Applying the Learner-Centered Micro Teaching Model for Improving Teaching Confidence, Attitudes Toward Teaching Profession, and Pedagogical Content Knowledge (PCK) of Physics Education Students (Jurnal Pendidikan Fisika, 2020)
The research on the use of the LCMT model aims to find out the increase in teaching confidence, attitudes toward the teaching profession, and pedagogical content knowledge (PCK) competencies of students.  The sampling technique uses purposive sampling and the number of individuals is 31 people consisting of 22 women and 9 men. Data obtained through questionnaires and assessment rubrics and tests. Questionnaires are used to measure teaching confidence and attitudes toward teaching profession. Assessment rubrics and tests are used to measure PCK. . Data were analyzed for normalized gain and paired t-test (paired sample test). The results showed a significant increase in teaching confidence with gain = 0.535 and t = 12.336 with sig. (2-tailed) = 0,000 (p
Keywords: Learner-center micro teaching; teaching confidence; LCMT; attitude toward teaching profession; pedagogical content knowledge; PCK